Perencanaan Strategi Pengembangan Usaha Produk Jamu - Suhartini, Sri; Effendi, Usman; Sukardi, Sukardi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2003)
Industrial jamu and traditional medicine are one of industrial that able to existing in the middle of Indonesian economic and political crisis. This is not released from some opportunities that faced such as: trend Indonesian community to using back the nature product (back to nature), abundant material, high price of chemical medicine, plenty of community chooses traditional medicine than modern and Indonesia has great population. But, their existing not released from some constrains that faced that are high competition both domestic and abroad especially from Chinese. The enlargement imitative jamu and mixed chemical material, and world medical attitude that not fully receiving the existing of industrial jamu and traditional medicine. Those constrains not minimize industrial jamu to develop its efforts, notify available big potency. In order to develop its effort then need to be made strategic planning to make industry operating effectively and efficiently to achieve the goal. SWOT analysis used to analyze strengths, weaknesses, opportunities and threats. Likert scale was using to obtain the priority or weight for each element in internal and external factors with range scale 1 – 5. SWOT analysis result revels that the best strategy at this moment is stabilized strategic through beware strategic, reminding the high level of competition. The alternative strategies using SWOT matrix are depending company’s image, depending and improving product quality, improving size and variation of product with diversification product, extended market area to the new market, developing distribution line, improving promotion, developing human resources, improving quality control, and using high technology. Key words: Strategic planning, Industrial jamu and traditional medicine, competitiveness.